Inside cells [ cells and their organelles - Garner, Simon , 1959-; Leigh, Richard , 1943-2007; Video Education Australasia (Australia : VEA Bringing Learning to Life, 2009)
This information-rich production takes viewers on a tour of 'cell gallery' and using illustrations of electron microscope imagery and graphics, looks in detail at the structure and function of cellular organelles, including cell membranes, nuclei, miochondria, chloroplasts, smooth and rough endoplasmic reticula, ribosomes, the Golgi complex, lysosomes, vacuoles, the cytoplasm, cytosol and cytoskeleton, microtubules and microfilaments.It covers the importance of internal cellular membranes and compares the relative sizes of the different organelles within a cell.
DVD
English
Keywords: Cell -- Study and teaching; Cytology